2020
DOI: 10.1111/1460-6984.12570
|View full text |Cite
|
Sign up to set email alerts
|

Falls in hospital patients with acquired communication disability secondary to stroke: A systematic review and meta‐analysis

Abstract: Background Falls are a common safety incident in people with stroke. Studies report that between 14% and 65% of people with stroke fall at least once during their hospital admission. Risk factors for falls in people with stroke have been reported to include neglect, balance and dependence for activities of daily living. Communication disability has been identified as a risk factor for patient safety incidents in hospital that has not been closely examined as a potential risk factor for falls in people with str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
(153 reference statements)
0
12
0
Order By: Relevance
“…The severity of and type of physical injury was reported in 13 studies (Baetens et al, 2011;Bugdayci et al, 2011;Byers et al, 1990;Chaiwanichsiri et al, 2006;Czernuszenko, 2007;Czernuszenko & Czlonkowska, 2009;Nyberg & Gustafson, 1996; et al, 2020et al, , Sze et al 2001). These difficulties could impact a patient's ability to understand and follow the instructions required to transfer, use equipment and ambulate safely, resulting in a fall (Mion et al, 1989;Nyberg & Gustafson, 1995;Zdobysz et al, 2005).…”
Section: Outcomes and Consequencesmentioning
confidence: 99%
“…The severity of and type of physical injury was reported in 13 studies (Baetens et al, 2011;Bugdayci et al, 2011;Byers et al, 1990;Chaiwanichsiri et al, 2006;Czernuszenko, 2007;Czernuszenko & Czlonkowska, 2009;Nyberg & Gustafson, 1996; et al, 2020et al, , Sze et al 2001). These difficulties could impact a patient's ability to understand and follow the instructions required to transfer, use equipment and ambulate safely, resulting in a fall (Mion et al, 1989;Nyberg & Gustafson, 1995;Zdobysz et al, 2005).…”
Section: Outcomes and Consequencesmentioning
confidence: 99%
“…It is estimated that communication disability (e.g., aphasia) affects approximately 64% of people with stroke, particularly those with left hemisphere stroke (Mitchell et al, 2020). Decreased ability to communicate with healthcare professionals can impact patient safety and the quality of care (Bartlett et al, 2008; Hemsley et al, 2013; Simmons-Mackie & Kagan, 2007; Sullivan et al, 2020). Patients with communication disability have unique factors that have the potential to contribute to falls in acute and rehabilitation hospitals, including problems communicating their basic needs (e.g., for using the toilet) and using the call bell to gain attention or assistance from staff (Hemsley et al, 2013; Sullivan & Harding, 2019; Sullivan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with communication disability are often excluded from falls research and where they are included, detailed reporting on communication disability is lacking (Hemsley et al, 2019). A recent systematic review and meta-analysis (Sullivan et al, 2020) found no association between communication disability and falls in acute or rehabilitation hospitals, but the included studies were limited by (a) failing to report on the severity of participants’ communication difficulties, and (b) excluding participants with severe strokes, a population more likely to experience both communication disability and falls (Mitchell et al, 2020; Sullivan et al, 2020). Subsequently, a review of prior research aiming to identify contributing factors, hazards, and outcomes of falls for patients with communication disability following stroke found no specific research to inform falls prevention strategies and further research (Sullivan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Falls are also connected with the level of functional dependence on activities of daily living (ADL) 11. ADL performance is one of the primary explanatory variables of falls in patients who have suffered a stroke 12.…”
mentioning
confidence: 99%
“…2,3 Falls have negative effects on the rehabilitation of patients who have suffered a stroke and increase the burden on family costs and the health care Falls are also connected with the level of functional dependence on activities of daily living (ADL). 11 ADL performance is one of the primary explanatory variables of falls in patients who have suffered a stroke. 12 Recently, a pictorial and innovative tool, the Longshi Scale (LS), was designed to evaluate ADL of individuals.…”
mentioning
confidence: 99%